Financing for development beyond Monterrey : contributions to a South agenda (South Centre GenevaCH, 2002)
Aims to contribute to the articulation of a South agenda on financing development, by briefly examining the changing sources and nature of external capital flows to developing countries, and addressing the question of their impact. Pinpoints some of the key current concerns of developing countries with regard to financing development. Provides a brief overview of the changing context regarding financing development. Outlines overview of the trends in capital flows, charting their changing composition over time; and a number of the factors which need to be taken into consideration when assessing the impact of foreign finance on developing countries.
Keywords: AID FINANCING